Acute effects of concurrent strength and endurance training on physiological and specific performance parameters in well-trained kayakers - Matzka, M.; Patterson, S.; Waldron, M.; Krakowski-Roosen, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The sport of Olympic sprint kayaking depends on both high aerobic and strength capabilities. Concurrent development of these components is a common training aim. However, concurrent training (CT) appears to have a negative impact on strength development, with no detrimental effects on endurance performance. García-Pallarés et al. (2010) proposed strategies to minimize these detrimental effects, one of which includes sequencing strength training before endurance workouts. Based on this recommendation, the aim of this study was to analyse whether hypertrophy strength training (HST) has negative effects on physiological performance parameters on a subsequent aerobic endurance bout in elite kayakers. Methods: Eleven well-trained youth kayakers had to perform two different training sequences in a randomized crossover design. One consisted of a HST performed before an aerobic endurance training (AET) that lasted 40 minutes at a velocity equal to 55% of VO2peak on an air-braked kayak ergometer with 20 minutes rest in-between. The second session included the AET without a preceding HST. Relative and absolute oxygen consumption, respiratory exchange ratio (RER), bloodlactate and stroke-rate data were collected every 10-minute interval during AET. Results: Wilcoxon test demonstrated no significant differences between training sequences for relative and absolute oxygen consumption, blood-lactate and stroke-rate during each interval and the entire endurance bout (P<0.05). RER differed between sequences in each of the four intervals with significantly (P<0.05) lower RER values in the AET bout that was subsequent to the HST session (HST+AET: 10` = 0,85; 20` = 0,0,87; 30` = 0,86; 40` = 0,85 / AET only: 10` = 0,88; 20` = 0,9; 30` = 0,89; 40` = 0,88). Discussion: Sequencing HST prior to AET may be a possible strategy to optimize concurrent training of strength and endurance. Especially, in the general preparation phase of sprint kayakers, where muscle growth and aerobic endurance capacity are major training aims, this sequencing may enable the athlete to produce favourable strength gains compared to an opposite sequencing. Lower RER after HST may even show a positive side effect of this order: Because of depleted glycogen storages consumption of fatty acids seems to be augmented. Future research should focus on long-term adaptations to this approach to examine this order effect on performance.